Carbon dot-based colorimetric sensor array for the discrimination of different water samples. Issue 43 (21st October 2019) - Shariati-Rad, Masoud; Ghorbani, Zahra
Abstract : Herein, a colorimetric sensor array has been introduced which uses carbon dots (CDs) to distinguish between different water samples. Abstract : Herein, a colorimetric sensor array has been introduced which uses carbon dots (CDs) to distinguish between different water samples. The basis of the method is that CDs interact differently with heavy metal ions in the presence of different water samples. The color change resulting from this interaction is recorded by a digital camera, and RGB values are analyzed by unsupervised and supervised chemometric methods, such as hierarchical cluster analysis (HCA), principal component analysis (PCA) and linear discriminant analysis (LDA). To increase the variables in the designed array, instead of using different CDs, the interaction of a single CD with different heavy metal ions and at different concentration levels is employed. The efficiency of the colorimetric sensor array in discriminating between deionized water and three real water samples was excellent. In addition to efficiency, the designed colorimetric sensor array is simple and inexpensive.